Analysis of the Factors Related Participatory Development from Perspective of Local Development Capacities in Ilam Provice - rahim mosavi; fereydoun vahida; Mansour haghighatian (توسعه اجتماعی, 2018)
This paper is prepared to identify and analysis of the factors related participatory development from perspective of local development capacities in Ilam province. The research method is quantitative and the kind of research is survey research. The ststistical population is 15-year-old people and higher than 15-year-old of Ilam province, the number of 432528 ones, and the sample size is 439 ones. Results from out research hub perspective the value of the pearson coefficient between human capital, economic capital, social capital, institutional capital variables and local capacity development to proceed the participation of the people in regional development of Ilam province was (0/358, 0/205, 0/311, 0/262, 0/437) positive and meaningful respectively. Also the results of tegression analysis affirms human capital variable Beta equal to 0/292 is the most amount, the second, institutional capital variable to the Beta equal to 0/182. the third, social capital variable to the Beta equal to 0/151 and the finally, economic capital variable to the Beta equal to 0/108 has fewest influence on to proceed the participation of the people in regional development of Ilam province. Generally, it can be concluded, human capital, economic capital, social capital, institutional capital, not only are factors contributing to the development of participment in the Ilam, but more importantly, the process of participartory development is a combination of these factors in the development.